Policing Protest : The Post-Democratic State and the Figure of Black Insurrection - Passavant, Paul A. (Paul Andrew) (Book collections on Project MUSE., 2021)
"Policing Protest explores how protest policing has become more hostile to protesters and how this hostility expresses a post-democratic state formation persistently haunted by the figure of black insurrection. Beginning in the late 1990s, a more violent style of protest policing took shape in the United States. This style of protest policing both criminalizes protest, and reacts to protests with increasing militarism where police fail to prevent or disorganize political mobilization critical of growing inequality and authoritarianism. "Security" is the protest policing arm of a distinctively post-democratic, post-legitimation state formation: neoliberal authoritarianism. This shift to protest policing that is more hostile to protesters is the result of reactions to three inter-related crises of the 1960s and 1970s: a crisis of democracy, the urban fiscal crisis, and the "crime" crisis. The institutional processes set in motion by these reactions converged by the late 1990s to create a more aggressive and violent style of policing protest. Each of these crisis reactions is haunted by the figure of Black insurrection, and this model of policing protest is particularly exemplified in the policing of #BlackLivesMatter protests"--